Pluralism in the Time of Postcolonialism: Cultural Diversity of Malay-Indonesian Archipelago in Upin-Ipin and Adit-Sopo-Jarwo (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
This paper aims to compare two animated series and critically look at the story elements which represent the plurality of the society. Recent studies commonly pointed out that Upin-Ipin (UI) and Adit-Sopo-Jarwo (ASJ) describe the genuine culture of the Malay-Indonesian archipelago, which is multiculturalism. Most scholars see cultural diversity in these animations as a fact. However, the study on reading a plurality of cultures as a value rather than a fact is rarely conducted. This study aims to analyze the works of two countries, Malaysia’s Les’ Copaque and Indonesia’s MD Animation, to demonstrate the inadequate category of cultural diversity as a ‘fact.’ Parekh’s theory of multiculturalism makes way to map and understand the plurality of society the series represent. At the same time, the cultural diversity presented in the series must be understood as a postcolonial pluralism landscape. By understanding the multicultural situation as postcolonial pluralism, this study concluded that first, multiculturalism in UI and ASJ performs cultural traces that derive from the country’s history, including colonialism. Second, multiculturalism in UI and ASJ is thick with ethnoreligious pluralism problem as a form of cultural penetration by European colonial, which is still apparent.